Development of redundant shoulder complex of human‐like robot driven by flexible wire tendons. Issue 20 (1st September 2014) - Choi, Taeyong; Lee, Joon‐Woo; Kim, Doohyung; Do, Hyunmin; Park, Dongil; Park, Chanhun
Abstract : For dual‐arm robot systems, which continue to become more common in the field of industrial robotics, a redundant shoulder complex could be very important to new developments. However, constructing a kinematically redundant shoulder complex is difficult because of spatial constraints. A novel redundant shoulder complex for a human‐like robot that is driven by flexible wire tendons against spatial constraints is proposed. The kinematically redundant shoulder complex allows the human‐like robot to generate more natural motions because of the availability of redundant degrees of freedom (DOFs), i.e. six DOFs per side. To control the proposed shoulder complex, a hybrid control scheme is used; the positioning precision was considered, and the ability of the shoulder complex to perform several human‐like motions was verified.